2019
DOI: 10.14260/jemds/2019/310
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Versus Ceftriaxone- Which Is Better in Uncomplicated Typhoid Fever? A Clinical Trial in a Tertiary Care Hospital

Abstract: BACKGROUND Enteric fever has been very a common and many times a fatal infective disease found in developing countries and has been known to have increasing resistance to novel drugs. So, there is an urgent need for a simple, therapeutic, cost-effective medicine to treat typhoid fever & to prevent further drug resistance. METHODS It is a non-randomized, case-control study done in Paediatrics department of Dr. Prabhakar Kore Hospital & Research centre of KAHER (KLE Academy of Higher Education and Research), att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…This comparative study between azithromycin and ciprofloxacin for uncomplicated enteric fever in children displayed high responsiveness of azithromycin with clinical efficacy more than 90%, resembling the results of many studies done previously. 8,18,19 Few studies reported the efficacy of azithromycin therapy in adults but not significant enough in children, contrary to our results where majority responded well to azithromycin. 20,21 The optimal dosing regimen of azithromycin for the treatment of enteric fever is yet to be determined.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This comparative study between azithromycin and ciprofloxacin for uncomplicated enteric fever in children displayed high responsiveness of azithromycin with clinical efficacy more than 90%, resembling the results of many studies done previously. 8,18,19 Few studies reported the efficacy of azithromycin therapy in adults but not significant enough in children, contrary to our results where majority responded well to azithromycin. 20,21 The optimal dosing regimen of azithromycin for the treatment of enteric fever is yet to be determined.…”
Section: Discussioncontrasting
confidence: 97%
“…6 Several trials have demonstrated azithromycin efficacy better with reduction of relapse, duration of hospital stay, clinical failure rate and well tolerated than many other competitive drugs. [7][8][9] In our region, though azithromycin and ciprofloxacin are amongst most commonly prescribed oral antibiotics in uncomplicated enteric fever as an empirical therapy but concerns persist regarding variations in response to treatment which is evident from a huge study carried out in Bangladesh. 10 Recently, many cases have been reported in Pakistan regarding extensively drug resistant strains of Salmonella typhi, responsible for a large typhoid outbreak.…”
Section: Introductionmentioning
confidence: 99%